Dissimilar laser welding of an AA6022-AZ31 lap-joint by using Ni-interlayer: Novel beam-wobbling technique, processing parameters, and metallurgical characterization. (15th April 2019) - Khodabakhshi, F.; Shah, L.H.; Gerlich, A.P.
Highlights: Beam wobbling technique was implemented during laser welding for the first time to join AA6022 and AZ31 dissimilarly. Nickel inter-layer was used to reduce the metallurgical incompatibility. Phase transformations during dissimilar metals intermixing inside the weld nugget region was studied. Mechanical performance of each interaction zone was elaborated in terms of indentation hardness resistance. Abstract: In this article, the weldability of dissimilar lap joints between 2 mm thick sheets of AA6022 aluminum (bottom) and AZ31 magnesium alloys (upper) was studied using a fiber laser with a wobbling scanner. The effects of laser beam wobbling parameters, laser power, traveling speed, and the presence of a pure nickel interlayer (∼0.1 mm thickness) is evaluated based on the microstructures and phases produced. The experimental results revealed dissimilar joint formation is highly dependent on inter-mixing, as well as fusion zone dimensions which control Al- and Mg-rich interaction zones that vary with laser power. Sound dissimilar joints were only produced by penetrating the Mg-rich interaction zone into the aluminum alloy. Joint formation benefited from suppression of Al-Mg chemical reactions using a Ni-interlayer, providing more well-dispersed and more benign phases compared to Al-Mg intermetallics at the interface during welding. The application of laser beam wobbling on a circular path with diameter of ∼0.4 mm and frequency of 1000 Hz served to reduce cracks and enhanced materials intermixing.